2011
DOI: 10.1111/j.1469-8986.2011.01184.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations of objectively measured physical activity with daily mood ratings and psychophysiological stress responses in women

Abstract: The aim of this study was to examine associations of objectively measured physical activity with daily mood ratings and psychophysiological stress responses. We recruited 40 healthy females (aged 28.7 ± 6.1 yrs) who completed a once-a-day mood rating scale for 7 days, along with a 7-day assessment of physical activity using accelerometers and psychophysiological stress testing. The findings suggest that levels of physical activity as measured using an accelerometer are associated with both depressive symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
39
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 58 publications
8
39
2
2
Order By: Relevance
“…Exercise may have beneficial effects on HPA functioning as some studies have shown lower stress-induced cortisol responses in physically trained individuals compared to the untrained (62,63). However, we failed to replicate previous findings in our work that examined associations between objectively assessed physical activity levels and cortisol responses to acute mental stress (29). In addition, recent data demonstrated higher levels of cortisol in the hair of trained athletes compared with controls, suggesting greater chronic exposure to cortisol in trained individuals (64).…”
Section: Physical Activity Stress and Inflammationcontrasting
confidence: 56%
See 2 more Smart Citations
“…Exercise may have beneficial effects on HPA functioning as some studies have shown lower stress-induced cortisol responses in physically trained individuals compared to the untrained (62,63). However, we failed to replicate previous findings in our work that examined associations between objectively assessed physical activity levels and cortisol responses to acute mental stress (29). In addition, recent data demonstrated higher levels of cortisol in the hair of trained athletes compared with controls, suggesting greater chronic exposure to cortisol in trained individuals (64).…”
Section: Physical Activity Stress and Inflammationcontrasting
confidence: 56%
“…Objective measures are not only able to assess intensity and duration of activity more effectively, but can also better delineate the duration of continuous bouts of activity 7 and periods of prolonged inactivity (sitting) (Figure 2). Very few studies have examined associations between objectively assessed physical activity and mental health, and those that have reveal inconsistent findings (25)(26)(27)(28)(29). Some of these limitations inherent to epidemiological studies can be reduced by investigations that use experimental manipulations of physical activity levels and those using stress reactivity paradigms.…”
Section: Epidemiological Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, depressive symptoms such as decreased energy or fatigue may directly affect self-reports of physical activity. 19 Only one study in Japan has used a form of objective measurement (an accelerometer) to assess physical activity, and this study reported a significant negative relationship between depressive mood and physical activity. 12 Pedometer is another tool for measurement of physical activity commonly used in other studies; however, it is not sensitive to slow activity or shuffling gaits 20,21 and it also motivates physical activity, 22,23 so it may either under or overestimate physical activity in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is well-established that naturally-occurring PA is largely associated with improved acute mood states [35][36][37] and better overall emotional functioning, such as lower depressive symptoms, 38,39 there are some contexts in which this effect has not been observed. For example, one study showed that engaging in higher levels of occupational PA was associated with worse depressive outcomes among adult women.…”
Section: Work Pamentioning
confidence: 96%